(untitled) (The Conference Hub, 2025)
Treating excessive tooth wear is a challenging task for dentists. This condition not only causes aesthetic problems and a loss of lower facial height, but also leads to functional disorders of the temporomandibular joint, tooth hypersensitivity, and malocclusion. Traditional orthopedic treatment involves fabricating onlays and crowns to cover worn teeth. The most conservative orthopedic treatment method is adhesively bonded ceramic veneers. However, the use of ceramic veneers is expensive, and if cracks or fractures develop in the long term, ceramic microprostheses cannot be repaired. Recently, much attention has been paid in medical literature to the therapeutic method of restoring teeth with excessive wear using direct composite restorations, which requires precise determination of the required space.